2021
DOI: 10.1038/s41598-021-94406-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and thermo-physical properties of highly stable graphene oxide-based aqueous nanofluids for potential low-temperature direct absorption solar applications

Abstract: Two types of highly stable 0.1% graphene oxide-based aqueous nanofluids were synthesised and investigated. The first nanofluid (GO) was prepared under the influence of ultrasonic irradiation without surfactant. The second nanofluid was treated with tetra ethyl ammonium hydroxide to reduce the graphene oxide to form reduced graphene oxide (RGO) during ultrasonic irradiation. The GO and RGO powders were characterised by various techniques such as field emission scanning electron microscopy, transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The linear fit was applied for the slope below and above the absorption edge of the composite Fe oxide/Fe hydroxide and Fe oxide/Fe hydroxide/N-rGO layers, the intersection of the two fitting lines giving the band gap energy 66 . For the pure GO6 layer a band gap range was determined, in accordance with reported data for rGO 67 . Similarly, the band gap range was estimated for the rGO containing composite samples.…”
Section: Resultsmentioning
confidence: 57%
“…The linear fit was applied for the slope below and above the absorption edge of the composite Fe oxide/Fe hydroxide and Fe oxide/Fe hydroxide/N-rGO layers, the intersection of the two fitting lines giving the band gap energy 66 . For the pure GO6 layer a band gap range was determined, in accordance with reported data for rGO 67 . Similarly, the band gap range was estimated for the rGO containing composite samples.…”
Section: Resultsmentioning
confidence: 57%
“…Moreover, in the GO spectrum, several peaks of higher intensity could be observed at 1718 cm −1 corresponding to the stretching vibrations of carbonyl groups [22], and at 1619 cm −1 assigned to the C=O stretching vibrations from carbonyl or carboxyl groups [23], but also to the physically adsorbed water molecules on or between the graphene sheets [24]. The peak at 1361 cm −1 corresponds to the stretching vibration of C=O group, while the one observed at 1222 cm −1 can be assigned to the stretching vibration of the C-O bond; the last was found in the GO-ATPES spectrum at 1220 cm −1 [25].…”
Section: Fourier Transform Infrared Spectrometry (Ft-ir)mentioning
confidence: 98%
“…An analysis of the existing data has shown that, in many cases, the presence of carbon nanomaterials in large quantities (mg/mL level) increases the thermal conductivity of the dispersion [28,[84][85][86]. As previously shown [27,78,[87][88][89][90], an increase in the GO concentration leads to an increase in k of the dispersion, which is the main reason for the increase in thermal diffusivity.…”
Section: Effect Of Graphene Oxide Concentration and Size On The Therm...mentioning
confidence: 81%